Mechanical Properties of Fully-Grouted Bolts Support Based on Compression Tests of Anchored Rock Mass - Tao Han; Changyu Jin; Guang Li; Qiang Wang; Lingyue Hou; Huiyang Liu (Applied Sciences)
The mechanical properties of fully-grouted bolt support are critical for the safety of support engineering works. To study the influences of factors including the bolt length and diameter, strength of the rock, and fracture angle on the mechanical properties of fully-grouted bolt support, compression tests were conducted on an anchored rock mass, considering the shortcomings of pullout tests on bolts. The discrete element software PFC2D (4.0) was adopted for numerical simulation and analysis from two aspects, namely, the stress distribution and anchorage force supplied by such bolts. The research found that by increasing the bolt diameter and length as well as the strength of the rock, the maximum anchorage force of bolts increases. Whereas the stress distribution of all bolts increases at first and then decreases along the bolts, and there is only one peak on the stress distribution curves, which also gradually shifts to a greater depth. In a fractured rock mass, the maximum anchorage force of bolts decreases, then increases (and is minimized at a fracture angle of 45°) with the decrease in fracture angle. The influence of fractures with different angles on the stress distribution of bolts is mainly reflected in the fracture zone. The bolt stress decreases abruptly in the zone with a fracture angle of 90°, forming a valley. The bolt stress increases suddenly in the zones with fracture angles of 60° and 45°, thus forming peaks. The bolt stress does not increase or decrease suddenly in the zone with a fracture angle of 30°. Therefore, it necessitates consideration of the influences of fractures on the anchorage force and the selection of bolts of appropriate size during anchorage design. After installation, the bolt stress should be monitored for stability and early warning of anchored rock mass according to changes in the stress provided.